2002
DOI: 10.1080/10473289.2002.10470842
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Size Distribution of Ultrafine Particles Near a Major Highway

Abstract: Motor vehicle emissions usually constitute the most significant source of ultrafine particles (diameter <0.1 µm) in an urban environment, yet little is known about the concentration and size distribution of ultrafine particles in the vicinity of major highways. In the present study, particle number concentration and size distribution in the size range from 6 to 220 nm were measured by a condensation particle counter (CPC) and a scanning mobility particle sizer (SMPS), respectively. Measurements were taken 30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
662
6
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 901 publications
(734 citation statements)
references
References 34 publications
55
662
6
11
Order By: Relevance
“…Comparison to Near-roadway and Ambient Concentrations Zhu et al (2002b) measured roadside concentrations of BC along the I-405 in LA, the same freeway traveled during bus commutes on U1 in our study, and found a mean concentration of 5.4 mg/m 3 next to the freeway, which reduced to 1.3 mg/m 3 at a site 300 m downwind of the freeway. The 300 m downwind concentration is comparable to the mean ambient BC concentrations we measured near either end of U1 of 1.3-2.9 mg/m 3 .…”
Section: Discussionsupporting
confidence: 53%
“…Comparison to Near-roadway and Ambient Concentrations Zhu et al (2002b) measured roadside concentrations of BC along the I-405 in LA, the same freeway traveled during bus commutes on U1 in our study, and found a mean concentration of 5.4 mg/m 3 next to the freeway, which reduced to 1.3 mg/m 3 at a site 300 m downwind of the freeway. The 300 m downwind concentration is comparable to the mean ambient BC concentrations we measured near either end of U1 of 1.3-2.9 mg/m 3 .…”
Section: Discussionsupporting
confidence: 53%
“…6 We did not include background pollutant concentrations because variability is likely low within the 13-km study radius. Dispersion-modeled gases are considered surrogates of other more toxic gases and particles emitted from nearby diesel trucks and automobiles, including ultrafine particles that have been found at notably higher concentrations near roadways along with black carbon, particle number, and CO. 29 The stronger associations for NO x compared with NO 2 support this because NO 2 is strongly affected by photochemical reactions that can occur across time away from roadways, whereas NO x is expected to capture traffic emissions more generally. 30 Key pollutants likely represented by NO x and CO are those carried by ultrafine particles.…”
Section: Overview Of Findings and Implicationsmentioning
confidence: 93%
“…Outdoor UFP concentrations were measured for 1-2 years in several US cities (U.S. EPA Supersites program; Solomon et al, 2008), and near roadways in California (Zhu et al, 2002) and also in Erfurt and Augsberg, Germany (Wichmann et al, 2000). Residential indoor concentrations have also been reported (Abt et al, 2000;Dennekamp et al, 2001;Long et al, 2001;Wallace and Howard-Reed, 2002;Klepeis et al, 2003;He et al, 2004;Wallace, 2000Wallace, , 2005Wallace, , 2006Wallace et al, 2004Wallace et al, , 2008Hoek et al, 2008).…”
Section: Introductionmentioning
confidence: 99%